53.2k views
1 vote
Someone help with this please!!!!

Someone help with this please!!!!-example-1

1 Answer

5 votes

Answer:


10^(4) * 10^(3)=(10*10*10*10)(10*10*10) = 10^(7)\\\\10^(4)*10^(4)=(10*10*10*10)(10*10*10*10) = 10^8\\\\(10*10*10)(10*10*10*10*10)=10^3*10^5=10^8\\


10^(18)*10^(23)= (10 x 10 18 times)(10 x 10 23 times)
=10^(41)

just as a note: when you multiply numbers with exponents and they both have the same base, all you have to do is add the exponents.

Ex:
10^(5)*10^(4)=10^(5+4)=10^(9)

User Niels Kristian
by
6.4k points